An analysis and critique of secured lending in South African law, including cession in securitatem debiti as a means to secure the repayment of loans for consumption - Kariem, Adnaan (Department of Commercial Law, 2022)
The thesis critiques South African secured lending laws by examining the contractual basis on which money is loaned and its repayment is secured, focusing on syndicated loans. The loan of money constitutes a loan for consumption in terms whereof the lender passes legal title to its money to the borrower, who must return the same number of units in the same currency, with or without interest. The law on loans for consumption is based on Roman law and Roman-Dutch law. The thesis analyses the principles whereby senior and mezzanine lenders, acting in a syndicate, lend money to a borrower in a loan for consumption where the repayments and security rights are ranked. The internationalisation of standard-form loan agreements is discussed, and some English law lessons are analysed. The principles that govern the legal nature, purpose and function of security rights in rem and in personam, and specifically security rights in syndicated loans, are analysed. In law, a security right is created when an asset is appropriated to a debt as contemplated by the common law and the Insolvency Act 24 of 1936. Security rights must be accessory to a valid principal debt. Insolvency law treats cessionaries as secured creditors and holders of guarantees as concurrent creditors. The principles of the law of cession, and the pledge and cession in securitatem debiti of rights in personam, including the theories that underly it, namely, the pactum fiduciae theory and the pledge theory, found security in personal rights and are measured against the United Nations Commission on International Trade Law (UNCITRAL) Model Law on Secured Transactions, Vienna, 2019, the English law on charges and Article 9 of the American Uniform Commercial Code. A number of deficiencies and inconsistencies in our security rights laws are identified, including incongruency, the absence of a coherent and uniform security rights system, and adverse insolvency law consequences for the cedent on the cessionary's insolvency arise from applying the pactum fiduciae theory. I conclude that the time is opportune to codify and reform South African law on secured lending to remedy the identified deficiencies and inconsistencies.